The amino acid transporter AAP1 mediates growth and grain yield by regulating neutral amino acid uptake and reallocation in Oryza sativa. (2nd June 2020) - Ji, Yuanyuan; Huang, Weiting; Wu, Bowen; Fang, Zhongming; Wang, Xuelu
Abstract : OsAAP1 positively regulates growth and grain yield in rice by influencing amino acid uptake and reallocation. Abstract: Nitrogen (N) is a major element necessary for crop yield. In most plants, organic N is primarily transported in the form of amino acids. Here, we show that amino acid permease 1 (AAP1) functions as a positive regulator of growth and grain yield in rice. We found that the OsAAP1 gene is highly expressed in rice axillary buds, leaves, and young panicles, and that the OsAAP1 protein is localized to both the plasma membrane and the nuclear membrane. Compared with the wild-type ZH11, OsAAP1 overexpression (OE) lines exhibited increased filled grain numbers as a result of enhanced tillering, while RNAi and CRISPR (clustered regularly interspaced short palindromic repeat; Osaap1 ) knockout lines showed the opposite phenotype. In addition, OsAAP1 -OE lines had higher concentrations of neutral and acidic amino acids, but lower concentrations of basic amino acids in the straw. An exogenous treatment with neutral amino acids promoted axillary bud outgrowth more strongly in the OE lines than in the WT, RNAi, or Osaap1 lines. Transcriptome analysis of Osaap1 further demonstrated that OsAAP1 may affect N transport and metabolism, and auxin, cytokinin, and strigolactone signaling in regulating rice tillering. Taken together, these results support that increasing neutral amino acid uptake and reallocation via OsAAP1 could improve growth and grain yield in rice.